2013
DOI: 10.1371/journal.pone.0062459
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Attenuates the Progression of Tau Pathology in P301S Tau Transgenic Mice

Abstract: Altered autophagy contributes to the pathogenesis of Alzheimer’s disease and other tauopathies, for which curative treatment options are still lacking. We have recently shown that trehalose reduces tau pathology in a tauopathy mouse model by stimulation of autophagy. Here, we studied the effect of the autophagy inducing drug rapamycin on the progression of tau pathology in P301S mutant tau transgenic mice. Rapamycin treatment resulted in a significant reduction in cortical tau tangles, less tau hyperphosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
132
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(148 citation statements)
references
References 37 publications
13
132
0
1
Order By: Relevance
“…Excitingly, rapamycin not only extends lifespan, it also prevents or delays the onset of age-related diseases such as cancer and Alzheimer’s disease, rejuvenates the aging mouse heart, and ameliorates age-related cognitive decline (Dai et al, 2014; Flynn et al, 2013; Majumder et al, 2012; Ozcelik et al, 2013; Spilman et al, 2010; Wilkinson et al, 2012). Unfortunately, rapamycin has been proven to have numerous negative side effects that would seem to preclude its wide-scale use as an anti-aging compound.…”
Section: Mtor Signaling In the Aging Processmentioning
confidence: 99%
“…Excitingly, rapamycin not only extends lifespan, it also prevents or delays the onset of age-related diseases such as cancer and Alzheimer’s disease, rejuvenates the aging mouse heart, and ameliorates age-related cognitive decline (Dai et al, 2014; Flynn et al, 2013; Majumder et al, 2012; Ozcelik et al, 2013; Spilman et al, 2010; Wilkinson et al, 2012). Unfortunately, rapamycin has been proven to have numerous negative side effects that would seem to preclude its wide-scale use as an anti-aging compound.…”
Section: Mtor Signaling In the Aging Processmentioning
confidence: 99%
“…The same mice, submitted to a 5-month long term preventive (3-week-old, asymptomatic mice) and to a 1.5-month short term therapeutic (3-monthold, diseased mice) treatment with rapamycin, show similar reduction (≥50%) of cortical tangles [80]. Rapamycin causes a brain area-dependent reduction of sarkosyl insoluble tau levels, and a marked increase of autophagy markers [80]. Rapamycin, when given at a low dosage between 1.5 and 3.5 months of age, reduces total tau levels and p-Ser181 tau levels in OXYS rats, and increases total S6K1 and p-S6K1 levels [81].…”
Section: Mtorc1mentioning
confidence: 84%
“…p-Ser9 levels on glycogen synthase kinase 3b (GSK-3b) are also reduced, linking mTORC1 inhibition-and GSK-3b inhibition-mediated reduction of HP-tau [79]. The same mice, submitted to a 5-month long term preventive (3-week-old, asymptomatic mice) and to a 1.5-month short term therapeutic (3-monthold, diseased mice) treatment with rapamycin, show similar reduction (≥50%) of cortical tangles [80]. Rapamycin causes a brain area-dependent reduction of sarkosyl insoluble tau levels, and a marked increase of autophagy markers [80].…”
Section: Mtorc1mentioning
confidence: 94%
“…For instance, rapamycin can inhibit mTORC1 activity and in turn upregulate autophagy. In a P301S mouse model, rapamycin can encouragingly reduce most hallmarks of tau disease, including phosphorylated tau levels, NFT formation and locomotion defects [220,221]. On the contrary, inhibition of autophagy through inhibitors such as 3-methylamphetamine (3-MA), or by genetic means such as removing ATG7 activity or upregulating mTORC1 activity, leads to a suppression of tau clearance [221][222][223].…”
Section: Molecular Chaperons Tau Clearance and Tau Toxicitymentioning
confidence: 99%
“…One possible approach to regulating tau levels is through changing mRNA stability or translation efficiency either via siRNA interference or pharmacologic compounds [271]; another approach to depress tau levels is through increasing protein degradation by stimulating the autophagy and/or proteasome pathway. It has been shown that autophagy activation with the use of rapamycin and trehalose significantly reduces tau levels [218,220]. Activating the proteasome to eliminate pathological tau proteins constitutes an alternative to autophagy.…”
Section: Regulation Of Tau Protein Level And/ or Immunotherapymentioning
confidence: 99%